Semiotika Ayat-Ayat Toleransi dalam Internalisasi Kerukunan di Indonesia - Huda, M. Masrur (Proceedings of Annual Conference for Muslim Scholars, 2024)
Tolerance is an attitude of respect between individuals in the diversity of the community. This view emphasizes the message of peace and harmony with other groups. The strong foundation of tolerance is humanism, which prioritizes humanity. However, this view should also be strengthened by semiotic-theological arguments that strengthen the semantic roots of tolerance in religious messages and human harmony. Some verses that are used as references in tolerance are found in several verses of the Qur'an with a variety of different editorials. For example, using the word as-salam, as-sulhu, al-islah which means peace, and/or harmony. This research is studying about 1) How is the semiotic form of the word tolerance in the verses of the Qur'an, and 2) How is the internalization of tolerance verses in the harmony of the people in Indonesia? The final result of this research is obtained, that semiotically-theological, the word tolerance is found in several verses of the Qur'an and the internalization of tolerance verses in the Qur'an becomes a key word used in religious harmony in Indonesia.